The dual role of microglia in Alzheimer’s disease: from immune regulation to pathological progression - He, Cong; Chen, Baojiang; Yang, Hecai; Zhou, Xiaoqing (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a widespread neurodegenerative disorder and one of the major challenges for public health. Despite extensive research, the role of microglia in AD remains complex and dual. The aim of this review is to summarize the most recent advances in research regarding the dual role of microglia in AD concerning both immunomodulation and pathological progression by considering mechanisms of activation of microglia, effects on Aβ clearance, tau pathology, and impacts due to genetic variations on microglial functions. Among these findings are the dual role of microglia, the status of activation for M1 and M2 phenotypes, and the crucial role that genetic variants like TREM2 have in modulating the response of microglia. This review describes how modulation of the microglial signaling pathway might be exploited therapeutically for AD treatment and underlines the relevance of a personalized medicine approach.